2020
DOI: 10.1002/cam4.2875
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of prognostic alternative splicing signature in hepatocellular carcinoma

Abstract: Previous studies have demonstrated the role of abnormal alternative splicing (AS) in tumor progression. This study examines the prognostic index (PI) of alternative splices (ASs) in patients with hepatocellular carcinoma (HCC). The clinical features and splicing events of patients with HCC were downloaded from The Cancer Genome Atlas (TCGA). Differentially expressed AS (DEAS) were compared between HCC and adjacent normal samples. Univariate Cox regression analysis was used to determine changes in DEAS associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
9
1
Order By: Relevance
“…The majority of favorable prognostic AS events (HR <1) were upregulated by SFs, whereas adverse AS events (HR >1) were downregulated. In contrast to observations in other cancers, this suggests that most of the SFs in PDAC inhibit tumor progression through the regulation of AS events [ 53 , 54 ]. However, owing to the lack of normal samples in TCGA, we were unable to identify differentially expressed SFs and draw comprehensive conclusions about the effects of SFs on PDAC.…”
Section: Discussioncontrasting
confidence: 64%
“…The majority of favorable prognostic AS events (HR <1) were upregulated by SFs, whereas adverse AS events (HR >1) were downregulated. In contrast to observations in other cancers, this suggests that most of the SFs in PDAC inhibit tumor progression through the regulation of AS events [ 53 , 54 ]. However, owing to the lack of normal samples in TCGA, we were unable to identify differentially expressed SFs and draw comprehensive conclusions about the effects of SFs on PDAC.…”
Section: Discussioncontrasting
confidence: 64%
“…Recently, a growing number of candidate biomarkers for diagnosis or prognosis of HCC have been identified [ 3 12 ], among which the most commonly reported biomarkers are dysregulated genes [ 3 , 6 , 11 ], significant members of a certain gene family or gene set [ 4 , 10 ], potential CpG methylation status [ 7 , 9 ], and alternative splicing signatures [ 5 , 12 ]. For example, a 24-mRNA-based risk signature has been developed as an independent risk classifier for the prediction of early recurrence in HCC patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on investigating the survival prognostic value of AS in cancers. Numerous studies have conducted SpliceSeq analyses to generate AS profiles for cancer prognosis monitoring with scores, including papillary thyroid carcinoma [ 39 ], colorectal cancer [ 40 ], non-small cell lung cancer [ 41 ], melanoma [ 42 ], hepatocellular carcinoma [ 43 ] and kidney cancer [ 44 ]. Our study added to the comprehensive understanding of patients with MM and identified survival-related AS signatures using high-throughput data.…”
Section: Discussionmentioning
confidence: 99%